Penggunaan Kosakata untuk Pencitraan Diri di Media Sosial Facebook - Nurlina Amirruddin; Sultan Sultan; Usman Usman (Nuances of Indonesian Language, 2022)
This study examines the use of vocabulary for self-image by users of social media facebook. This study aims to: (1) describe the form of exponential vocabulary for self-image on social media facebook; (2) describe the form of relational vocabulary for self-image on social media facebook; (3) describe the form of expressive vocabulary for self-image on social media facebook. This study uses a qualitative descriptive approach by using a type of critical discourse analysis research. The critical discourse analysis model used is Fairclough's critical discourse analysis model. This study uses qualitative descriptive research design that focuses on the research process and results. The data in this study were sourced from posts by Facebook social media users. Data collection techniques were carried out in two stages, namely: observation and documentation. The results of the study reveal that the forms of the expansive vocabulary found in this study are classification, ideological words that are fought for, lexicalization, synonyms, antonyms, hyponyms, and metaphors. The forms of relational vocabulary found in this study are euphemistic expressions, formal words, informal words, greetings, names, and personal references. The forms of expressive vocabulary found in this study are in the form of positive evaluation and negative evaluation. The use of vocabulary forms for self- image is used to support efforts to build self-image carried out on Facebook social media by Facebook social media users.